Almost disarmed: Politics and violence in the final years of the Argentine organization Montoneros (1979–1983). Issue 2 (October 2021) - Slipak, Daniela
In this article, I analyze the debates, declarations, and silences surrounding the issue of violence during the final years of the Argentine insurgent group Montoneros (1979–1983). I examine the official documents and bulletins written while the group was in exile, as well as the statements and publications of dissident groups (the Peronismo Montonero Auténtico of 1979 and the Montoneros 17 de Octubre of 1980) and other critical groups (the Agrupación Eva Perón of 1980). From a political theory perspective, I will focus on the specificity of this space of belonging, its symbols, its representations, and its actions. In this study, I intend to (a) shed light on the final stage of the Montoneros organization, which, with few exceptions, has not been subjected to historiographical or sociological analysis, or studied by political science and (b) contribute to a deeper understanding of the dissolution processes undergone by armed insurgent groups in Latin America in the 1960s and 1970s.